2010
DOI: 10.1097/qad.0b013e32833bb732
|View full text |Cite
|
Sign up to set email alerts
|

Acute HIV-1 infection is highly prevalent in Ugandan adults with suspected malaria

Abstract: Objectives Acute febrile illnesses consistent with malaria are the most common presentation at health clinics in sub-Saharan Africa, accounting for 30–50% of outpatient visits. The symptoms of acute human immunodeficiency virus (HIV) infection can mimic acute malaria. We investigated whether acute HIV infections could be identified among adults with suspected malaria at rural health centers in Uganda. Design Cross-sectional study of 1,000 consecutive patients referred for malaria blood smears at each of 7 go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 30 publications
2
33
1
Order By: Relevance
“…This finding shows that the burden of HIV infection in Nigeria is still a cause for concern particularly among febrile individuals seeking healthcare at various hospitals. Our finding among these febrile participants was similar to the study by Bebell et al [13] who reported a similar prevalence of HIV among adults who sought care for suspected malaria in Uganda. Likewise, and also in 2010, Serna-Bolea et al [20] reported that 3.3% of patients who sought care for fever at a district hospital in Southern Mozambique had acute HIV infection.…”
Section: Figure 1: the Percentage Distribution Of Positive Samples Frsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding shows that the burden of HIV infection in Nigeria is still a cause for concern particularly among febrile individuals seeking healthcare at various hospitals. Our finding among these febrile participants was similar to the study by Bebell et al [13] who reported a similar prevalence of HIV among adults who sought care for suspected malaria in Uganda. Likewise, and also in 2010, Serna-Bolea et al [20] reported that 3.3% of patients who sought care for fever at a district hospital in Southern Mozambique had acute HIV infection.…”
Section: Figure 1: the Percentage Distribution Of Positive Samples Frsupporting
confidence: 81%
“…Furthermore, Bebell et al reported in 2010, that 1-3% of adults who sought care for suspected malaria in Uganda actually had acute or early HIV infection [13] . Considering the surge in HIV-1 replication and viral load in individuals with ARS, who are highly contagious and the fact that such persons may not be aware of their status.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are often asymptomatic or experience a nonspecific febrile illness; a diagnostic dilemma compounded in the African setting by a significant symptom overlap with malaria. 3,9 To diagnose AHI, the presence of the virus itself must be detected by nucleic acids or proteins in the absence of HIV-specific antibodies. Fourth-generation HIV assays have demonstrated good sensitivity and specificity for detecting HIV infection and AHI but remain less sensitive than nucleic acid amplification technology.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study Anastos et al reported higher risk in CIN3+ HIV+ women in Rwanda who had recently acquired the malaria parasite (Anastos et al, 2010). Co-infection with malaria in HIV-1 patients dysregulates the immune system (Bebell, Pilcher, Dorsey, et al, 2010). Bebell et al observed that acute HIV-1 infections occurred in high HIV prevalence regions of Uganda with low malaria endemicity (Bebell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Co-infection with malaria in HIV-1 patients dysregulates the immune system (Bebell, Pilcher, Dorsey, et al, 2010). Bebell et al observed that acute HIV-1 infections occurred in high HIV prevalence regions of Uganda with low malaria endemicity (Bebell et al, 2010). Kelly and Rickinson in their review of Burkitt's lymphoma pathogenesis emphasized the significance of HIV-1 and malaria (Kelly & Rickinson, 2007).…”
Section: Introductionmentioning
confidence: 99%